THE EFFECT OF POPULATION, LABOR FORCE ON ECONOMIC GROWTH IN OIC COUNTRIES - Fitri Utami; Fani Monada Essa Putri; Muhammad Ghafur Wibowo; Budi Azwar (Riset Ekonomi Pembangunan, 2021)
The population has an important role in accelerating or slowing down the economic growth of a country. This study aims to examine the effect of the male and female population and labor force on economic growth. The objects of this study were 5 OIC countries in the period 2010-2019. The method used in this research is panel data regression analysis. Researchers found that population size has a significant negative impact on economic growth. Meanwhile, the number of the labor force has a significant positive effect on increasing economic growth. However, the male labor force has a significant negative effect and the female workforce has a significant positive effect in increasing economic growth in 5 OIC (Indonesia, Pakistan, Egypt, Nigeria, and Bangladesh) during the 2010-2019 period.